Understanding Online Zakat Payment Decisions: The Roles Of Accountability, Technology Adoption, And Religiosity - Bunga Cinta Dian Winata; Sitti Aisya; Rizki Amalia (Journal of Contemporary Economics and Business Management, 2026)
The rapid development of digital technology has encouraged the use of online platforms for zakat payment. However, studies examining the effects of accountability and technology adoption on zakat payment decisions, with religiosity as a moderating variable, remain limited, particularly among muzakki in Palu City, Indonesia. This study aims to analyze the effects of accountability and technology adoption on the decision to pay zakat through online platforms and to examine the moderating role of religiosity in these relationships. A quantitative approach was employed using a survey method involving 100 muzakki who use online zakat platforms in Palu City. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that technology adoption and religiosity have a positive and significant effect on online zakat payment decisions, while accountability has no significant effect. Furthermore, religiosity does not significantly moderate the relationships between accountability and online zakat payment decisions, nor between technology adoption and online zakat payment decisions. These findings suggest that the convenience, usefulness, and efficiency of technology, together with the level of religiosity, are the primary factors influencing muzakki’s decisions to use digital zakat services